Study on Relationship between Emotional Intelligence and Self Actualization among Academicians of Tamil Nadu Universities - R. , Gopinath (International Journal of Psychosocial Rehabilitation, 2020)
Every profession needs a certain set of skills to fulfill their professional responsibilities. Teaching is a profession in which the academician needs to prepare himself before entering the teaching profession. They require a lot of patients even for classroom management; they are in the position to handle the emotions of young adolescents. This makes emotional intelligence very important for academicians. Self-actualization means actualizing one’s own capabilities, becoming everything one is capable of becoming. Self-actualized individuals are also thought to be correlated with higher levels of emotional intelligence, better outcomes at work, and better general health and well-being in the quest for personal development. Emotional intelligence refers to being effective, and self-actualization to doing the best you possibly can. Being both emotional intelligence and self-actualization is considered important for academicians, the researcher attempted to study the influence of emotional intelligence on the self-actualization of academicians in Tamil Nadu universities. 175 samples were collected through the Purposive Stratified Random Sampling technique. The researcher found a significant and positive influence of emotional intelligence on the self-actualization of academicians at Tamil Nadu universities.